A high frequency missense SULT1B1 allelic variant (L145V) selectively expressed in African descendants exhibits altered kinetic properties. (2nd January 2018) - Tibbs, Zachary E.; Guidry, Amber L.; Falany, Josie L.; Kadlubar, Susan A.; Falany, Charles N.
Abstract: 1. Human cytosolic sulfotransferase 1B1 (SULT1B1) sulfates small phenolic compounds and bioactivates polycyclic aromatic hydrocarbons. To date, no SULT1B1 allelic variants have been well-characterized. 2. While cloning SULT1B1 from human endometrial specimens, an allelic variant resulting in valine instead of leucine at the 145th amino acid position (L145V) was detected. NCBI reported this alteration as the highest frequency SULT1B1 allelic variant. 3. L145V frequency comprised 9% of 37 mixed-population human patients and was specific to African Americans with an allelic frequency of 25%. Structurally, replacement of leucine with valine potentially destabilizes a conserved helix (α8) that forms the "floor" of both the substrate and PAPS binding domains. This destabilization results in altered kinetic properties including a four-fold decrease in affinity for PAP (3′, 5′-diphosphoadenosine). Km s for 3′-phosphoadenosine- 5′-phosphosulfate (PAPS) are similar; however, maximal turnover rate of the variant isoform (0.86 pmol/(min*μg)) is slower than wild-type (WT) SULT1B1 (1.26 pmol/(min*μg)). The L145V variant also displays altered kinetics toward small phenolic substrates, including a diminished p-nitrophenol Km and increased susceptibility to 1-naphthol substrate inhibition. 4. No significant correlation between genotype and prostate or colorectal cancer was observed in patients; however, the variant isoform could underlie specific pathologies in sub-Saharan African carriers.